Ask the GBV experts - Koma Akim; Nyakomi Adwok (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2023)
In the course of preparing this issue on gender-based violence, some questions arose, so we asked the two experts in the SSMJ Editorial Board: Dr Koma Akim, a general and obstetric fistula surgeon working in Bor State Hospital in South Sudan, and Dr Nyakomi Adwok, a psychiatrist with working experience in the UK and Kenya.